Contribution to sampling procedure of gold-bearing geological materials - Dempír, Josef (Univerzita Pardubice, 1999)
If the gold particles in material to be analyzed are distributed homogeneously and follow the Poisson law, the sample weight necessary for analytical work can be easily estimated using the sampling constant according to Ingamells. With gold particles distributed heterogeneously, Visman's equation are used for the same purpose. In the present paper both approaches are described and their practical use is shown on two gold-bearing ores, one with homogeneously and the other with heterogeneously distributed gold particles.
Keywords: zlato; stanovení zlata; vzorky rud; Analýza; Atomová absorpční spektrometrie